PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN DENGAN MENGGUNAKAN APLIKASI CANVA BAGI GURU-GURU SMA AL-FALAH HMM TIMIKA - Rasul, A.; Yantika, Nurmalsari; Jamila, Jamila (Jurnal Pengabdian Masyarakat Nasional, 2023)
So far, teachers at SMA Al-Falah HMM Timika have not been able to make learning videos using the Canva application. Therefore, training was carried out on making learning videos with the application. This community service activity was carried out with the aim of designing learning videos using the Canva application by Al-Falah HMM Timika High School teachers. The methods of this activity are lectures, presentations, assignments, and questions and answers. All of these methods are applied face-to-face (offline). The number of teachers who participated in this activity was 18 people. The activity was carried out in one day, namely on Saturday, January 14 2023. Based on observations, it was known that the participants took part in the activity with great attention and enthusiasm. They are willing to follow the steps for making learning videos. Other than that, the videos that are made are quite good. The design of the video is quite varied. In general, the participants were able to make videos with an average score of 3.70 in the good category. So, this community service activity was successfully held because it enabled the participants to make learning videos with the Canva application.